Ki67 and p53 expression in relation to clinicopathological features in phyllodes tumour of the breast - Ali, Nurul Atiah Mohd (2020)
Introduction: Phyllodes tumour is a rare fibroepithelial neoplasm of the breast. Histopathological features remained the gold standard for the diagnosis. The usage of immunohistochemical markers of Ki67 and p53 acts as a supplement method particularly for the malignant phyllodes tumour. Therefore we aim to study the expression of these markers in phyllodes tumour and to see its relation to the tumour grading. Methodology: This was a retrospective cross-sectional study conducted on 57 numbers of archival tissue samples from the year 2015 to the year 2018 from the laboratory of Hospital Universiti Sains Malaysia and Hospital Sultanah Nur Zahirah. The histopathological examinations were analysed and further immunohistochemistry markers of Ki67 and p53 protein expression were studied on formalin-fixed paraffin embedded tissue. Result: The study showed that there was an association between clinical descriptive data of skin changes, lump size of more than 3 cm, cytological atypia, stromal hypercellularity, mitosis and immunohistochemistry with the clinical diagnosis of phyllodes tumour. Both marked expression of Ki67 and p53 are seen in borderline and malignant phyllodes tumour. However the presence of both high mitosis and marked expression of Ki67, on top to other histological features, was merely seen in case of malignant PT. Conclusion: In our study, there were a significant association of both p53 and Ki67 expression in case of borderline and malignant phyllodes tumour. Nevertheless, with presence of high mitotic rate and strong expression of Ki67 index are exclusively found in malignant phyllodes tumour. Further study of a larger sample size and division into more precise of low-high grade group is recommended for a validated result. On top of that, it is also helpful to predict the prognosis as well as the disease-free-survival of the tumour.